Yetkisiz temsilcinin sorumluluğu - Işık, Egemen (My University, 2024)
Temsil olunan, yetkisiz temsilci tarafından yapılmış sözleşmeyi onamadığında, yetkisiz temsilcinin sorumluluğu söz konusu olur. Yetkisiz temsilcinin sorumluluğu, Türk Borçlar Kanunu’nun 47. maddesinde ve kaynak İsviçre Borçlar Kanunu’nun 39. maddesinde düzenlenmiştir. Sorumluluğun unsurları, Türk Borçlar Kanunu’nun 47. maddesinde iki fıkrada düzenlenmiştir. Temsil olunanın sözleşmeyi onamaması hâlinde sözleşme geçersiz olur ve bu sözleşmenin tarafı olan üçüncü kişi, sözleşmenin geçersizliği sebebiyle uğramış olduğu zararın tazminini yetkisiz temsilciden talep edebilir. Bu çalışmada, hükmün uygulanması sırasında ortaya çıkan hukuki sorunlar tespit edilecek ve bu sorunlara yönelik çözüm önerileri sunulacaktır.

When the principal does not ratify the agreement, which the agent without authority has entered into, then the agent incurs liability. The liability of the unauthorized agent has been regulated under Article 47 of the Turkish Code of Obligations, which was adopted from the Article 39 of Swiss Code of Obligations. The conditions of the liability have been arranged in two subparagraphs under Article 47. When the principal does not ratify the agreement, then the contract will be invalid and the unauthorized agent will be liable for damages to the third party. With regard to implementation of the Article 47 of Turkish Code of Obligations, there have been many issues in practice and this dissertation will concentrate upon these legal issues and try to suggest legal solutions to these problems.
Liability of an agent without authority
Keywords: Culpa in contrahendo; Hukuk; Law; Liability (law); Özel hukuk; Power of attorney; Private law; Sorumluluk (hukuk); Sözleşme öncesi kusur; temsil; Temsil yetkisi; unauthorized agent; unauthorized representation; yetkisiz temsil; yetkisiz temsilci representation